Binding of Coagulation Factor XIII Zymogen to Activated Platelet Subpopulations: Roles of Integrin αIIbβ3 and Fibrinogen - Kotova, Yana N.; Podoplelova, Nadezhda A.; Obydennyy, Sergey I.; Kostanova, Elizaveta A.; Ryabykh, Alexander A.; Demyanova, Aleksandra S.; Biriukova, Maria I.; Rosenfeld, Mark A.; Sokolov, Alexey V.; Chambost, Herve; Kumskova, Maria A.; Ataullakhanov, Fazoil I.; Alessi, Marie-Christine; Panteleev, Mikhail A. (Thrombosis and Haemostasis, 2019)
Factor XIIIa (fXIIIa) is a transglutaminase that plays a crucial role in fibrin clot stabilization and regulation of fibrinolysis. It is known to bind to procoagulant platelets. In contrast, the zymogen fXIII interaction with platelets is not well characterized. We investigated the interaction of zymogen fXIII with activated platelet subpopulations. Confocal microscopy and flow cytometry using fluorescently labelled factors and antibodies. Phosphatidylserine (PS)-positive activated platelets bound 700 to 800 molecules/cell of fXIII at 100 nM, while both PS-negative activated platelets and resting platelets bound 200 to 400 molecules/cell. The binding was reversible, calcium-independent and linear within the fXIII concentration range of up to 1,000 nM. fXIII predominantly bound to the caps of procoagulant platelets and co-localized with fibrinogen. Exogenous fibrinogen promoted fXIII binding by activated PS-negative platelets; this effect was abolished by the integrin αIIbβ3 antagonist monafram. The fXIII binding was 1.5- to 3-fold decreased for platelets from four patients with grey platelet syndrome, and was variable for platelets from six patients with Glanzmann's thrombasthenia. Strong platelet stimulation, fibrinogen and αIIbβ3 play essential roles in fXIII binding, without any of them fXIII does not bind to platelets. The preferential binding in the cap-like structures might be important for increasing local fXIII concentration in platelet thrombi.
Keywords: factor XIII; platelet sub-populations; integrin αIIbβ3; fibrinogen; Glanzmann's thrombasthenia